Evaluation of the Arkansas Tobacco Settlement Program Progress Through 2011 - Summary - Engberg, John (RAND Corporation, 2012)
In 2001, Arkansas ranked 45th of 50 states on a composite score of all health outcomes. Arkansas is now a regional leader in tobacco control. This summary of the final biennial report documents the Arkansas Tobacco Settlement Commission's continued activity and progress, and gauges the effectiveness of the state's seven health-related programs in the past decade. Included is an evaluation of the changes in health outcomes attributed to these programs.